Iron‐Incorporated α‐Ni(OH)2 Hierarchical Nanosheet Arrays for Electrocatalytic Urea Oxidation - Xie, Junfeng; Liu, Weiwei; Lei, Fengcai; Zhang, Xiaodong; Qu, Haichao; Gao, Li; Hao, Pin; Tang, Bo; Xie, Yi (Chemistry : a European journal, 2018)
An iron‐incorporated α‐Ni(OH)2 nanosheet array catalyst characterized by hierarchical surface nanobelts and robust urea oxidation performance are reported. The unique single‐crystalline belt‐on‐sheet hierarchical nanostructure was identified and it endows more reactive edges for the Ni2+‐to‐Ni3+ pre‐oxidation process to boost the generation of active high‐valence species for the urea oxidation reaction (UOR). Benefitting from the optimal Fe concentration, the UOR activity was further optimized owing to the favorable reaction kinetics. With the synergistic benefits of the increased surface areas, improved charge transfer behavior, favorable reaction kinetics and excellent structural stability, the iron‐incorporated α‐Ni(OH)2 hierarchical nanosheet array catalyst displays significantly improved UOR performance with both high activity and outstanding operational stability. This work could guide the design of advanced UOR catalysts for wastewater treatment and clean energy production in the future. An iron belt: A hierarchical belt‐on‐sheet iron‐incorporated α‐Ni(OH)2 nanosheet array catalyst was developed. This catalyst exhibits increased surface areas, improved charge‐transfer behavior, favorable reaction kinetics, and excellent structural stability for robust urea oxidation.